A generic green solvent concept boosting the power conversion efficiency of all-polymer solar cells to 11%. Issue 1 (29th November 2018) - Li, Zhenye; Ying, Lei; Zhu, Peng; Zhong, Wenkai; Li, Ning; Liu, Feng; Huang, Fei; Cao, Yong
Abstract : Advances in organic photovoltaic technologies have always been closely associated with a deeper understanding of bulk-heterojunction (BHJ) microstructure morphology, which is generally governed by the ink-formulation based on a single solvent or solvent mixtures. Abstract : Advances in organic photovoltaic technologies have always been closely associated with a deeper understanding of bulk-heterojunction (BHJ) microstructure morphology, which is generally governed by the ink-formulation based on a single solvent or solvent mixtures. The relatively slow progress in all-polymer solar cells (all-PSCs) is mainly due to the significant difficulty in mastering their intricate BHJ morphology dealing with entanglements of polymer chains, limiting their performance typically to 8–10%. In this work, we demonstrate that the performance of all-PSCs can be further developed to a benchmark value of 11% by manipulating the BHJ morphology using a green solvent system based on cyclopentyl methyl ether (CPME). The generic applicability of the superior ink-formulation is successfully validated in four different all-polymer solar cells, exhibiting great promise of advancing all-PSCs towards industrial production and commercialization.